Search and Context - Dumais, Susan (2014)
Understanding a short search query in isolation is a very difficult task. Query understanding is much easier if we consider the "context" in which the query arises, e.g., previous queries the searcher has issued, the current location and time, etc. Traditionally search engines have returned the same results to everyone who asks the same question. However, using a single ranking for everyone, in every context limits how well a search engine can do. I begin by outlining a framework to characterize the extent to which different people have the same (or different) intents for a query. I then describe several examples of how we represent and use context to improve search quality. Finally I conclude by highlighting some challenges in developing contextually-aware algorithms including evaluation.
Keynote at CLEF 2014